KDELC2 Upregulates Glioblastoma Angiogenesis via Reactive Oxygen Species Activation and Tumor-Associated Macrophage Proliferation - Yu-Ling Tsai; Ying Chen; Ying-Chuan Chen; Wen-Chiuan Tsai (MDPI AG, 2023)
Glioblastoma is notorious for its rapid progression and neovascularization. In this study, it was found that KDEL (Lys-Asp-Glu-Leu) containing 2 (KDELC2) stimulated vasculogenic factor expression and induced human umbilical vein endothelial cell (HUVEC) proliferation. The NLRP3 inflammasome and autophagy activation via hypoxic inducible factor 1 alpha (HIF-1α) and mitochondrial reactive oxygen species (ROS) production was also confirmed. The application of the NLRP3 inflammasome inhibitor MCC950 and autophagy inhibitor 3-methyladenine (3-MA) indicated that the above phenomenon activation correlated with an endothelial overgrowth. Furthermore, KDELC2 suppression decreased the endoplasmic reticulum (ER) stress factors' expression. The ER stress inhibitors, such as salubrinal and GSK2606414, significantly suppressed HUVEC proliferation, indicating that ER stress promotes glioblastoma vascularization. Finally, shKDELC2 glioblastoma-conditioned medium (CM) stimulated TAM polarization and induced THP-1 cells to transform into M1 macrophages. In contrast, THP-1 cells co-cultured with compensatory overexpressed (OE)-KDELC2 glioblastoma cells increased IL-10 secretion, a biomarker of M2 macrophages. HUVECs co-cultured with shKDELC2 glioblastoma-polarized THP-1 cells were less proliferative, demonstrating that KDELC2 promotes angiogenesis. Mito-TEMPO and MCC950 increased caspase-1p20 and IL-1β expression in THP-1 macrophages, indicating that mitochondrial ROS and autophagy could also interrupt THP-1-M1 macrophage polarization. In conclusion, mitochondrial ROS, ER stress, and the TAMs resulting from OE-KDELC2 glioblastoma cells play important roles in upregulating glioblastoma angiogenesis.